PERANCANGAN PENILAIAN ESAI OTOMATIS DENGAN KNUTH MORRIS PRATT - Jesica Jesica; Viny Christanti M (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Designation of automated essay scoring with Knuth Morris Pratt is an application used to score essay automatically. Essay in this application is Indonesian essay. The main process of this system is SyntacticSemantic Similarity that is supported with tagging process and Knuth Morris Pratt method to score essay. Stanford POS tagging is used in POS tagging process for Indonesian. This application can be used by teachers and students. This system compares students’ answers and key answers. Next step, system get the score based on the similarity of the answers. The score from the system gives quite good result but it still has weakness. System cannot produce perfect score even though all essay is answered correctly. Average score of 50 right answers is 99.739 and average score of 50 imperfect answers is 76.1 with average time is 1.51 seconds. Key words automated essay scoring, Knuth Morris Pratt, syntactic semantic similarity, Stanford POS tagging